Characterisation of Phytochemical Content of Seagrass Ethanol Extract Using Gas Chromatography Mass Specrometry (GC-MS) - Wahyuni, Sri; Hasanah, Uswatun; Sulaiman, Ismail; Munandar, Munandar; Rizal, Muhammad (Jurnal Perikanan Terpadu, 2024)
Research on the bioactive potential of marine biological resources is increasingly growing, especially in marine plants such as seagrasses that produce secondary metabolites. This study aims to characterize the phytochemical content of the ethanol extract of Thalassia hemprichii seagrass from Lhok Timon beach, Aceh Jaya, using the Gas Chromatography-Mass Spectrometry (GC-MS) method. The main issue addressed is the lack of quantitative data on the phytochemical composition of this seagrass, particularly secondary metabolites. Extraction was conducted using the maceration method with 96% ethanol, followed by GC-MS analysis to identify bioactive compounds. The analysis results revealed 38 compounds, with D-Fructose, diethyl mercaptal, pentaacetate as the dominant one, displaying potential biological activities such as antimicrobial, antioxidant, anti-inflammatory, and antifungal properties. Other significant compounds include fatty acids and phenols that support antioxidant activity. The discussion emphasizes the potential development of these compounds for pharmaceutical and industrial applications, given their bioactive properties. In conclusion, T. hemprichii seagrass contains promising phytochemicals for further development as bioactive agents in the health sector